IMMUNOSTIMULATORY EFFECT OF OCIMUM SANCTUM LINN. LEAF EXTRACT IN CLARIAS BATRACHUS LINN - Nahak, Gayatri; Sahu, Rajani Kanta (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Recently, there has been increased interest in the immune stimulating function of some herbs in aquaculture. The phytomedicines provide a cheaper source for treatment and greater accuracy than chemotherapeutic agents without causing toxicity. Many studies have proved that herbal additives enhanced the growth of fishes and protected them from various diseases. The herbs are not only safe for consumers but also widely available throughout the world and they also have a significant role in aquaculture. Certain medicinal plants are believed to promote positive health and maintain organic resistance against infection by re-establishing body equilibrium and conditioning the body tissues. Methods: The aerial parts ofÂ Ocimum sanctumÂ Linn. were extracted with double distilled water and then extracts were screened for their immunomodulatory effects on Clarias batrachus. Haematological and biochemical studies were done on specific and nonspecific levels after administering the extracts for 15 and 30 days. Result: Our results showed that there is no significant decrease in the amount of glucose and cholesterol at concentration 2.5% but there is a significant reduction in glucose amount at 5% in comparison to control. But a significant increase was seen; the RBC, WBC, serum protein and globulin at 2.5% and 5% concentrations of crude extracts in both the 15 and 30 days of treatments in the blood of the fish. It may be due to the presence of phenolic compounds like tannins, saponin, flavonoids, steroid, terpenoids, eugenol, caryophylline, cardiac glycerides etc. Conclusion: Based on the results it is appropriate to conclude that the plant extract of Ocimum sanctum may act as a potent Immunostimulant in Clarias batrachus Linn. Keywords: Immunostimulants, Phytochemicals, Clarias batrachus Linn, Ocimum sanctum Linn.